Da or weil, daher or deswegen? / Because it is not adequate for the target language...? That’s why! Target language adequacy of causal adverbs in L1- and L2-Texts in German - LAURENTZEN, CHRISSY; JENTGES, SABINE (Glottodidactica, 2017)
Grammar books for L2-learners mostly follow grammatical themes, e.g. sentence – verb – conjunctions. However, when a L2-learner composes a text, he will probably focus more on the function he wants to express than the form he wants to use. In this article, functionality versus grammatical categories will be discussed in order to answer the question, whether and – if so – how German and Dutch students differ in their way of expressing causality in academic writing. An analysis of German Bachelor’s and Master’s theses written by German and Dutch students showed differences between these groups in their use of subcategories (word classes) and specific words for expressing causality. The absence of a functional structure and specific information about the use of causal connectives in grammar books can therefore be regarded as an important cause for these findings. Especially for advanced L2-learners of German it seems recommendable to organize grammar books to put a greater focus on function (rather than form).